Analysis of the Use of Instagram as a Publication Media in Building a Brand Image of @Kurve.official - Stephanie Lauren; Hanny Saputri; Shekinah Magda (Budapest International Research and Critics University, 2022)
Businesses are increasingly using instagram as a publication tool to reach their target audience due to its rapid growth. Instagram's various features and benefits have made publishing even easier. However, because of the intense competition among businesses on this platform, brands must have a positive brand image in order to be chosen by the audience. @Kurve.official is an Indonesia-based online business that sells women’s clothing and uses Instagram as their main social media platform. This research aims to analyze how @Kurve.official utilizes Instagram as their publication media in building the brand image. The main theory used in this research is a theory by Chris Heuer that talks about social media utilization 4C (context, communication, collaboration, and connection). The methodology is qualitative with a descriptive approach. The conclusion is the use of @Kurve.official Instagram in building its brand image is in line with the 4C theory which can be seen from the message, the communication that occurs, the collaboration between KURVE and its audience, and the efforts to maintain the established relationship with the audience. The suggestions given are to optimize the hashtag, content’s concept, Instagram Live, and automatic message.